Circulating Levels of Dimethylarginines, Chronic Kidney Disease and Long-Term Clinical Outcome in Non-ST-Elevation Myocardial Infarction - Cavalca, Viviana (Public Library of Science, 2012)
BACKGROUND: Mechanisms linking chronic kidney disease (CKD) and adverse outcomes in acute coronary syndromes (ACS) are not fully understood. Among potential key players, reduced nitric oxide (NO) synthesis due to its endogenous inhibitors, asymmetric (ADMA) and symmetric (SDMA) dimethylarginine could be involved. We measured plasma concentration of arginine, ADMA and SDMA and investigated their relationship with CKD and long-term outcome in non-ST-elevation myocardial infarction (NSTEMI). METHODOLOGY/PRINCIPAL FINDINGS: We prospectively measured arginine, ADMA, and SDMA at hospital admission in 104 NSTEMI patients. CKD was defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m(2). We considered a primary end point of combined cardiac death and re-infarction at a median follow-up of 21 months. In CKD (n = 33) and no-CKD (n = 71) patients, arginine and ADMA were similar, whereas SDMA was significantly higher in CKD patients (0.65±0.23 vs. 0.42±0.12 µmol/L; P<0.0001). Twenty-four (23%) patients had an adverse cardiac event during follow-up: 12 (36%) were CKD and 12 (17%) no-CKD patients (P = 0.02). When study population was stratified according to arginine, ADMA and SDMA median values, only SDMA (median 0.46 µmol/L) was associated with the primary end-point (P = 0.0016). In models adjusted for age, hemoglobin and left ventricular ejection fraction, the hazard ratio (HR) for CKD and SDMA were high (HR 2.93, interquartile range [IQR] 1.15–7.53; P = 0.02 and HR 6.80, IQR 2.09–22.2; P = 0.001, respectively) but, after mutual adjustment, only SDMA remained significantly associated with the primary end point (HR 5.73, IQR 1.55–21.2; P = 0.009). CONCLUSIONS/SIGNIFICANCE: In NSTEMI patients, elevated SDMA plasma levels are associated with CKD and worse long-term prognosis.